Local and systemic effects of cat allergen nasal provocation. Issue 3 (March 2015) - Scadding, G. W.; Eifan, A.; Penagos, M.; Dumitru, A.; Switzer, A.; McMahon, O.; Phippard, D.; Togias, A.; Durham, S. R.; Shamji, M. H.
Summary Background Cat allergen is widely distributed in homes and schools; allergic sensitization is common. Objective To develop a model of cat allergen nasal challenge to establish dose–response and time–course characteristics and investigate local and systemic biomarkers of allergic inflammation. Methods Nineteen cat‐allergic individuals underwent titrated nasal challenge, range 0.243 to 14.6 μg/mL Fel d1, and matched diluent‐only provocation. Clinical response to 8 h was assessed by symptom scores and peak nasal inspiratory flow (PNIF). Nasal fluid was collected using polyurethane sponges and analysed by ImmunoCAP and multiplex assays. Whole blood flow cytometry for basophil surface CD63, CD107a, and CD203c was carried out at baseline and 6 h post‐challenge. Results A dose–response to allergen was seen in symptom scores and PNIF, maximal at 10 000 BU/mL (4.87 μg/mL Fel d1), P < 0.0001 vs. diluent. Nasal fluid tryptase was elevated at 5 min after challenge (P < 0.05 vs. diluent); eotaxin, IL‐4, ‐5, ‐9, and ‐13 were increased at 8 h (P < 0.05 to P < 0.0001 vs. diluent); TSLP was undetectable; IL‐10, IL‐17A, and IL‐33 were unchanged compared to diluent challenge. Nasal fluid IL‐5 and IL‐13 correlated inversely with PNIF after challenge (IL‐5, r = −0.79, P < 0.0001; IL‐13, r = −0.60, P = 0.006). Surface expression of CD63 and CD107a was greater at 6 h than at baseline, both in the presence (both P < 0.05) and absence (CD63, P < 0.01; CD107a, P < 0.05) of in vitro allergen stimulation; no changes were seen on diluent challenge day. Conclusions Cat allergen nasal challenge produces local and systemic Th2‐driven inflammatory responses and has potential as a surrogate outcome measure in clinical trials.